Pengaruh Efikasi Diri, Persepsi Profesi Guru dan Lingkungan Sosial Terhadap Minat Menjadi Guru Ekonomi - Lilis Wulandari; Heni Purwa Pamungkas (Jurnal Pendidikan Ekonomi (JUPE), 2022)
This research aims to analyze the effect of self-efficacy, perception of the teaching profession and social environment on teacher interest, either partially or simultaneously. This study used quantitative methodology and involved 60 students of Economic Education Study Program UNESA as respondents. Data analysis technique used regression analysis. The research revealed that self-efficacy affected interest to be a teacher by 49.7%, then, teacher proffesion perception affected only 27.4%, and the social environment affected only 17.1%.